Mechanisms connecting square dance to sleep quality among middle-aged and older Chinese females: serial mediation roles of social support and depressive symptoms - Jun Wu; Yong Yu; Keke Qin; Zhiwen Ou (Frontiers Media S.A., 2023)
BackgroundSquare dance is gaining increasing popularity among middle-aged and older Chinese women who are also at high risk of sleep disturbance. Although previous studies have shown exercise could improve sleep quality, the association between square dance and sleep quality remains to be discussed, and even less is known about the potential mechanism underlying this association.PurposeThis study aims to investigate the relationship between square dance and sleep quality and test if social support and depressive symptoms together play a serial mediating role in the influence of square dance on sleep quality.MethodsA cross-sectional study was conducted among 549 middle-aged and older Chinese females from September to December 2020 in Shao Yang City, Hunan Province of China, with ethics approval granted (SYU [2020]002). Square dance involvement was assessed by three questions about the time participants spent in square dance. Social support, depressive symptoms, and sleep quality were measured using the Pittsburgh Sleep Quality Index (PSQI), Social Support Self-Rating Scale (SSRS), and 9-item Patient Health Questionnaire (PHQ-9), respectively. The serial mediation model was analyzed by the bootstrapping method to assess whether social support and depressive symptoms mediate the relationship between square dance and sleep quality.ResultsTwo-thirds of the participants had high involvement in square dance and most reported a moderate and high level of social support (98.54%). The prevalence of depressive symptoms and sleep disturbance was 19.49 and 26.78%, respectively. The serial mediation model showed a significant association between square dance and sleep quality, which was fully mediated by social support and depressive symptoms in a serial model (total effect c = −0.114, 95%CI = −0.227 to −0.001; direct effect c' = −0.036, 95% CI = −0.138 to 0.065; total indirect effect ab = −0.077, 95% CI = -0.139 to-0.016).ConclusionOur study extends the understanding of how square dance is associated with sleep quality through the serial mediating roles of social support and depressive symptoms. It provides crucial implications for developing square dance interventions to improve sleep quality among middle-aged and older Chinese females.